Regional Financial Performance and Fiscal Independence Strategies in Baubau City - Muhammad Rezky Alfajrin; Ahmad Juanda; Rizki Febriani (SAINTIS Publishing, 2025)
Fiscal decentralization in Indonesia aims to strengthen the capacity of local governments to manage financial resources independently, yet its implementation continues to face major challenges. Baubau City is among the regions with low fiscal independence, where the contribution of locally generated revenue (PAD) remains weak and reliance on central transfers is still dominant. This study evaluates the financial management performance of Baubau City during 2019–2023 using four main indicators: the fiscal independence ratio, the fiscal decentralization ratio, the routine capacity index, and the fiscal dependency ratio. A mixed-methods approach was applied, combining quantitative analysis of budget realization reports (APBD) with qualitative insights from in-depth interviews with officials at BPKAD and Bapenda. The findings show that the average fiscal independence ratio was 12.21 percent (low), fiscal decentralization 9.6 percent (very poor), routine capacity 10.72 percent (very poor), and fiscal dependency 85.97 percent (very high). These results indicate that fiscal autonomy in Baubau City has not been substantively realized. Institutional weaknesses limited human resources, low taxpayer compliance, and the underuse of digital systems exacerbate the situation. Strengthening fiscal institutions, updating tax databases, adopting digital technology, and optimizing sectors such as tourism, maritime services, and regional trade are necessary to improve fiscal independence and achieve sustainable regional development.